Offensiveness of controversial products for students of three different fields of study in Brazil - Frade, João Lucas Hana; Oliveira, Jorge Henrique Caldeira de; Giraldi, Janaina de Moura Engracia (Revista de Administração da UFSM, 2021)
Purpose: investigate the offensiveness of controversial products in Brazil, especially the influence of the field of study. Design/methodology/approach: a questionnaire with 11 controversial products was conventionally answered by a sample of 368 college students from the three most popular fields of study in Brazil (i.e. Human Sciences, Biological and Health Sciences, and Exact and Technological Sciences). The offensiveness of each controversial product was measured and compared across those fields of study through t-tests. Findings: Controversial products did not easily offend respondents being guns, weight-loss medicine, and female underwear the most offensive ones. In general, students of Human Sciences are the most easily offended and those of Exact and Technological Sciences the least offended. In addition, results showed differences and similarities between people from each field of study. Originality/value: Improvement of our knowledge about controversial products in Brazil, especially about the influence of the field of study in the offensiveness of controversial products.